Development of Legal Aspects in the Beauty and Care Products Industry - Carmelita Carmelita (Fakultas Hukum Dehasen, 2024)
The beauty and care products industry has experienced rapid growth in recent years, both at national and international levels. This growth brought attention to legal issues related to safety, quality, and ethics in the production, distribution, and marketing of beauty and care products. So it is not surprising that there are many cases of the beauty industry and care products that violate the law and cause a stir in Indonesia. Even though consumers are getting smarter and demanding clear and accurate information about the beauty products they use, because the beauty industry business is very lucrative from a profit standpoint, there are still many individuals who have bad intentions and justify any means to gain as much profit as possible. magnitude. The journal aims to identify and analyze legal aspects related to this industry as well as provide views on legal developments necessary to protect consumers and ensure product safety. This journal aims to identify and analyze legal aspects related to this industry and provide views on developments. This journal uses normative juridical research methods by collecting and analyzing data from various legal sources, including laws, regulations, government policies, and court decisions related to the beauty industry and care products in Indonesia.